Prevalence of low Back Pain among Street Cleaners in Northeastern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Street cleaners assume bending and twisting positions for a long period while on the job, making them to be susceptible to low back pain (LBP).Aims:This study was aimed at determining the prevalence of LBP among street cleaners in North-eastern Nigeria.Settings and Design:Sample of convenience was to recruit 381 participants who were street cleaners working within Maiduguri Metropolitan Council.Subjects and Methods:A conveniently sampled participants (n= 381) completed sociodemographic form, Nordic LBP Questionnaire and LBP risk factors form. Descriptive statistics were used to summarise the data, and Chi-square statistics were used to explore the differences in LBP prevalence by sociodemographics.Results:The present study shows a 12-month LBP prevalence rate of 78.2% and a crude point (7 days) prevalent rate of 55.1% among the workers, and this condition tend to occur more frequently among those in the age group between 58 and 67 years than their counterparts in the lower age groups (P= 0.001). Male cleaners tend to report LBP more frequently than their female counterparts (P= 0.011), and those with primary or qur’anic education also reported LBP more frequently than their counterparts with secondary or tertiary education (P= 0.046). Performing the same task over and over and working in the same position for long periods were the most frequently chosen risk factors pre-disposing the workers to LBP on their job.Conclusions:The present study identified the needs for workers ergonomic education and employers’ consideration for ergonomically fit tools, as potential solution to addressing LBP as an occupational hazard among the workers.